49.2k views
3 votes
Someone help please

Someone help please-example-1

2 Answers

3 votes

Explanation:

Hey, there!

Here,


= 4 {x}^(2) - 4x + 1


or ,\: ( {2x)}^(2) - 2.2x .1 + 1


or ,\: ( {2x - 1)}^(2)

We got this because,


( {2x - y)}^(2) = 4 {x}^(2) - 4x + 1

By using formula,


( {x - y)}^(2) = {x}^(2) - 2xy + 1

Hope it helps..

User Joshuapoehls
by
5.7k points
4 votes

Answer: (x+-0.5)²=0

Explanation:

4x²-4x+1=0

(2x-1)²=0 ⇔ completing the square

--------------------------------------------

since the question asked for the x should be 1, then we should divide 2x by 2 so to get rid of the 2 in front of the x.

this will change the original equation into: (x+(-0.5))²=0

------------------------------------------------------------------------------------------------------------

You can also directly divide 4 from 4x²-4x+1=0 to get rid off the terms in front of x.

x²-x+0.25=0

(x-0.5)²=0

(x+(-0.5))²=0

User Andras Zoltan
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.